Investigating the Relationship between Rumination and Negative Affect with Early Maladaptive Schemas in Students - Bazargani, Maedeh; Moraveji, Mahtab; Asadi, Masoud (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: Early maladaptive schemas are one of the most important psychological characteristics, and rumination and negative affect are important variables related to primary maladaptive schemas. This present study aims to determine the relationship between rumination and negative affect and primary maladaptive schemas in students of Islamic Azad University in Zanjan. Methods: This descriptive research is correlational. The statistical population studied in this research included all male and female students of Islamic Azad University, Zanjan branch, who are studying in different fields and levels in the academic year of 2021-2022, which includes 14,000 people, which is a multi-stage random sampling method. They were selected. In the current research, Yang's schema questionnaire, Watson's negative affect effects, and Hoeksma and Maro's rumination were used to collecting data. The method of data analysis was Kolmogorov-Smirnov tests, Pearson's correlation coefficient, and stepwise regression, using SPSS 24 software. Results: To predict rumination based on early maladaptive schemas in students, those who selected only vulnerability, deprivation, isolation, and rejection schemas from among the early maladaptive schemas were able to explain 13.0% of the variance in rumination in four steps. To predict negative affect based on early maladaptive schemas in students, those who selected only vulnerability, entitlement, and attention-seeking schemata from among the early maladaptive schemas were able to explain 17.0% of the variance in negative affect in three steps. Pearson's correlation results are significant at the 0.001 level to investigate the relationship between rumination and negative affect with primary maladaptive schemas in students. Conclusions: Based on the results of the research, it can be concluded that rumination and negative affect are related to primary maladaptive schemas. This is because primary maladaptive schemas predict rumination and negative affect.